Twelve Million Black Voices: Let Us Now Hear Black Voices - Laurence Cossu-Beaumont (Transatlantica)
Twelve Million Black Voices is a 1941 collection of photographs, selected from the Farm Security Administration files by FSA-employed Edwin Rosskam and accompanied by Richard Wright’s texts. This paper examines the specificity of Twelve Million Black Voices within the frame of American documentary photography. The first part of this paper considers the original place of a photo-text book on black life in a decade of “documentary literature” (Kazin, 1942, 493). The second part raises the question of the social, economic and political reality exposed by the widespread publication of photographs of –invisible– black Americans. Ultimately the paper will extend the reflection on “truth” in the narrative. A “folk history” is carefully crafted, or perhaps staged, by the weaving of text and photographs. This paper thus strives to articulate the recording of 1930s reality and the exposure of racial discrimination, the aesthetic vision of FSA photographers and the protest narrative unfolded by Wright by discussing the singular way Twelve Million Black Voices manages to signify the truth of the African American reality.